Novel methods for earth fault passage indication in non-effectively grounded electricity distribution networks - Farughian, Amir (Vaasan yliopisto, 2022)
Electricity distribution networks are commonly subject to supply interruptions and outages caused by faults. This dissertation focuses on medium voltage distribution networks, which typically consist of primary substations having multiple feeders along which secondary substations are located. When a permanent fault occurs on a segment (the part linking two consecutive secondary substations) of a distribution feeder, the faulted segment needs to be identified and isolated. Identifying the faulted segment can be realized through fault passage indicators. This is a straightforward task when the fault type is a short circuit, as these types of faults involve large currents. However, faulted segment identification for earth faults in non-effectively grounded medium voltage distribution networks has remained a challenge as the earth fault current in those networks is typically relatively small. Therefore, the main objective of this dissertation was to develop novel methods for locating single-phase earth faults in medium voltage distribution networks and validating them through simulations and real system measurements. After comprehensive review of state-of-the-art approaches presented in the literature, the dissertation proposes innovative methods for earth fault passage indication aimed at non-effectively grounded urban or rural distribution networks with radial feeders. The proposed methods are underpinned by a theoretical analysis based on the symmetrical components of the currents on a distribution feeder under an earth fault condition. The comparison of the sequence currents collected from various measuring points on the network forms the backbone of the methods. For practical implementation, current measurements need to be transferred to a central location for processing and decision making, but this can be done without accurate time synchronization. The proposed methods were developed and verified through simulations and empirical data. This work is a product of close collaboration between academia and industry that enabled the validation of the proposed methods with the help of empirical data that was provided by system operators and relay manufacturers. The results obtained from simulations and field tests show the efficacy of utilizing sequence current quantities, in the manner proposed in this work, for identifying the passage of earth faults with fault resistances ranging from zero to several kilo-ohms. In practice, the methods are reliable as long as the current measurements are accurate enough.

Sähkönjakeluverkoissa esiintyy vikoja, jotka aiheuttavat sähkönjakelun keskeytyksiä eli sähkökatkoja. Tämä väitöskirja käsittelee keskijänniteverkkoja, jotka koostuvat sähköasemista ja niiltä lähtevistä johtolähdöistä. Johtolähtöjen varrella sijaitsevat pienjänniteverkkoa syöttävät muuntamot. Kun jollain johto-osuudella (tässä ns. muuntamovälillä, joka yhdistää kaksi peräkkäistä muuntamoa) ilmenee pysyvä vika, viallinen johto-osuus on tunnistettava ja erotettava. Viallisen johto-osuuden tunnistaminen tapahtuu vianilmaisimien avulla. Viallisen johto-osuuden tunnistaminen on yksinkertaista, kun vikatyyppi on oikosulku, sillä oikosuluille ominaista ovat yleensä suuret vikavirrat. Haasteena on kuitenkin edelleen viallisten johto-osuuksien tunnistaminen maasulkutilanteissa ei-tehollisesti maadoitetuissa keskijänniteverkoissa, joissa maasulkuvirta on tyypillisesti hyvin pieni. Tämän väitöskirjana tavoitteena on ollut kehittää uusia menetelmiä maasulkuvikojen paikantamiseen keskijänniteverkossa ja varmentaa niiden toimivuus simuloinnein ja todellisesta verkosta saatujen mittausten avulla. Kattavan kirjallisuuskatsauksen jälkeen tässä väitöskirjassa esitellään innovatiivisia menetelmiä vikavirran reitin ilmaisuun jakeluverkkojen maasuluissa. Ehdotetut menetelmät tukeutuvat teoreettiseen analyysiin, jossa johtolähdön virrat maasulkutilanteessa on kuvattu symmetristen komponenttien avulla. Menetelmät perustuvat verkon eri pisteissä mitattuihin virran symmetristen komponenttien vertailuun. Käytännön toteutuksessa nämä mittaukset tulee siirtää keskitettyyn järjestelmään prosessointia ja päätöksentekoa varten, mutta tämä voidaan tehdä ilman tarkkaa aikasynkronointia. Ehdotettujen menetelmien kehittämisessä ja testaamisessa hyödynnettiin simulointeja ja kokeellista mittausdataa. Yhteistyö teollisuuden kanssa mahdollisti menetelmien toiminnan todentamisen hyödyntäen todellisista verkoista mitattua dataa, jota saatiin sekä verkkoyhtiöiltä että laitevalmistajilta. Simulointien tulokset ja mittaukset todellisessa verkossa tehdyistä testeistä osoittavat, että virran symmetriset komponentit toimivat hyvin vian paikannuksessa kun vikaresistanssi on nollan ja muutaman tuhannen ohmin välillä. Käytännössä menetelmien luotettavuus riippuu virran mittauksen tarkkuudesta.
Keywords: distribution of electricity; electrical engineering; electrical power networks; defects; voltage; measuring methods; electric circuits; faults; smart grids; data communications networks; fi=Sähkötekniikka|en=Electrical Engineering|